The low energy problem on astrophysics braneworld - Ovalle, Jorge (Ciencia)
Considering an anisotropic and non uniform stellar distribution in the context of braneworld, an exact analytic solution to Einstein”™s field equations is found, however it is not possible to regain the low energy limit. To find the source of this “low energy limit problem” a careful analysis on an isotropic and no uniform distribution is performed. It is shown that the source of the problem is the KK corrections to the field equations of general relativity